Evaluation of the German living guideline “Protection against the Overuse and Underuse of Health Care” – an online survey among German GPs - Lisette Warkentin; Martin Scherer; Thomas Kühlein; Felix Pausch; Dagmar Lühmann; Cathleen Muche-Borowski; Susann Hueber (BMC Primary Care)
Abstract Background The aim of this study was to evaluate the awareness and use of the German guideline “Protection against the overuse and underuse of health care” from the general practitioners’ (GPs’) perspective. In addition, the study assessed how GPs perceive medical overuse and what solutions they have for reducing it. Methods We performed a cross-sectional online survey with recruitment from 15.06. to 31.07.2023. Participants were members of the German College of General Practitioners and Family Physicians (DEGAM). The main outcomes were the awareness and use of the guideline. Results The analysis included data from 626 physicians. 51% were female and the median age was 50 years. The guideline is known by 81% of the participants, 32% read it in more detail. The majority considered the guideline a helpful tool in reducing overuse (67%). Almost 90% wished to have more guidelines with clear do-not-do recommendations. Physicians indicated in mean (M) that 30.2% (SD = 19.3%) of patients ask them for medical services that they do not consider to be necessary and that M = 30.2% (SD = 18.1%) of all GP services can be attributed to medical overuse. About half of the participants thought that overuse is a moderate or major problem in their practice (52%) and in general practice overall (58%). More participants rated that it is especially a problem in specialist (87%) and inpatient care (82%). Changes in the reimbursement system, raising awareness for the problem and more evidence-based guidelines were considered helpful in mitigating overuse. Conclusions Although the guideline is seen as a useful tool in mitigating medical overuse, there is still further potential for its implementation and utilisation. GPs see more overuse in the inpatient and outpatient specialist areas than in their area of practice. Instead of self-critically approaching the problem, the proposed strategies are aimed at the healthcare system itself.